2001
DOI: 10.1086/319686
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Infection Induces Virus Expression in Human Immunodeficiency Virus Transgenic Mice by CD4 T Cell–Dependent Immune Activation

Abstract: To test the capacity of malaria parasites to trigger virus expression in vivo, human immunodeficiency virus (HIV) transgenic mice were infected with Plasmodium chabaudi chabaudi clone AS. Splenocytes recovered during peak parasitemia showed a dramatic elevation in viral p24 production that returned to baseline by day 15 and failed to rebound at recrudescence or after reinfection. The major sources of virus expression were antigen-presenting cells (APCs) rather than T lymphocytes. Nevertheless, T cells from inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…The experimental system we used in this study involves infection of HIV-Tg mice with the malaria parasite P. chabaudi. Previous experiments demonstrated that this protozoan rapidly induces increased expression of HIV proteins and mRNA in spleen and increased p24 antigenemia in parallel with the acute phase of parasitemia (34). In our model, production of HIV p24 was found to be dramatically elevated in DC and M isolated from P. chabaudi-infected animals compared with that in uninfected mice and, importantly, was shown in this study to be associated with up-regulated CD40 expression on the same cells.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The experimental system we used in this study involves infection of HIV-Tg mice with the malaria parasite P. chabaudi. Previous experiments demonstrated that this protozoan rapidly induces increased expression of HIV proteins and mRNA in spleen and increased p24 antigenemia in parallel with the acute phase of parasitemia (34). In our model, production of HIV p24 was found to be dramatically elevated in DC and M isolated from P. chabaudi-infected animals compared with that in uninfected mice and, importantly, was shown in this study to be associated with up-regulated CD40 expression on the same cells.…”
Section: Discussionsupporting
confidence: 65%
“…Although proinflammatory cytokines are probably implicated in the up-regulated virus expression following P. chabaudi infection through the induction of CD40 on APC, their neutralization did not decrease microbial-induced viral expression (34), ruling out a direct role in the activation of APC. Interestingly, in the case of hepatitis B virus-Tg mice, malaria-induced proinflammatory cytokines have the opposite role, causing the suppression of hepatitis B virus replication and gene expression, emphasizing the distinct mechanisms regulating transgene expression in these two viral models (38).…”
Section: Discussionmentioning
confidence: 88%
“…The failure of HIV-1 to penetrate mouse cells can be circumvented by constructing mice transgenic for an infectious provirus derived from HIV-1, such as the X4 laboratory isolate NL4-3 (1,37). These transgenic mice have been used to investigate in vivo activation of HIV-1 in monocytes by pathogens (10,14,21,25), the efficacy of treatments that block proviral expression (55,56), and the role of Toll-like receptors in the pathogen-induced activation of the HIV LTR (2,16). To enable study of the behavior of primary HIV-1 isolates, we expanded upon this approach by developing a different mouse line that is transgenic for HIV-1 JR-CSF , a full-length HIV-1 provirus derived from the well-characterized primary R5-tropic clinical isolate (9,49).…”
mentioning
confidence: 99%
“…Upon exposure to Toxoplasma gondii (8), Plasmodium chabaudi (9), or M. avium (10), these animals display enhanced expression of HIV-1 transcripts as well as p24 (a capsid protein encoded by the gag gene) and assemble small numbers of infectious viral particles detected by coculture with human T cell lines. In the case of T. gondii infection, such activation of HIV-1 gene expression was found to be markedly reduced in control Tg mice in which the NF-B region of the long-terminal repeat (LTR) (3) was inactivated by sequence substitution (8).…”
mentioning
confidence: 99%